Analisis Kesulitan Siswa dalam Memahami Konsep Asas Black pada Pembelajaran Fisika - Masara, Apriyanti; Gunantiani, Justiciya Martan; Rohman, Silmi Maulani (Jurnal Pendidikan dan Ilmu Fisika, 2024)
Conceptual understanding is a fundamental aspect of physics education. However, Black’s Principle, which relates to heat transfer and thermal equilibrium, often poses challenges for students. This study aims to identify students' difficulties in understanding this concept at a Madrasah Aliyah in Garut Regency. This research utilized a case study approach involving 16 eleventh-grade students and their physics teacher as key participants. Data were collected through classroom observations, interviews, questionnaires, and conceptual understanding tests, then analyzed thematically and using descriptive statistics. The results indicate that only 35% of students correctly understood Black’s Principle before implementing interactive learning methods, but this increased to 76% after the intervention. The main obstacles identified included misconceptions about heat transfer, the dominance of lecture-based teaching methods, and the limited use of experiments and technology-based learning media. This study recommends the integration of simple experiments, digital simulations, and discussion-based problem-solving approaches to enhance students' comprehension. The findings provide valuable insights for educators in developing more interactive and exploratory teaching strategies in physics education.